Aplicações das cadeias de Markov na previsão de precipitações pluviométricas - Pscheidt, Fabio (2020)
In this work, a mathematical model is presented to determine the probability of daily rainfall in the counties of Cuiabá and Diamanino, located at Mato Grosso State. The model is developed based on the concepts of Markov Chains, which was fed with daily rainfall information obtained from the INMET - National Institute of Matereology website, which monitors and records data from the automatic stations in Cuiabá and Diamantino. The presentation of the concepts for the elaboration of the model is aimed at high school students, showing that the combination of elementary mathematical concepts are capable of providing sophisticated mathematical models. The results obtained indicated that the mathematical model developed was able to determine a probability over the specified rainfall values and that the model can be explored during mathematics classes to encourage students to deepen their knowledge in mathematics and technology.